The important of information integration in marine management: a review - Tarmidi, Mohammad Zakri; Mohamed Shariff, Abdul Rashid; Mahmud, Ahmad Rodzi; Zaiton Ibrahim, Zelina (IDOSI Publications, 2013)
The integration between marine information management is important for a sustainable marine management. It will balance the impact to environmental, social and economic of marine area. Several marine management and marine information management has been research and develop, such as integrated coastal zone management, marine protected area, marine ecosystem based management, marine spatial data infrastructure, marine cadastre and marine risk management. But this initiative has been develop isolated between each other, whereas, it resulting in autonomous, heterogeneous and distributed management. With integrated information management, it will help in enabling rapid and right decisions through an environmental, social and economical way. It also will bring together the diverse communities that involved in marine management.